Social policy and health: deterioration of informal work due to COVID-19, the case of taxi drivers in Mexico (Revista de Investigaciones Universidad del Quindío, 2021)
The objective of this work is to describe the effects of the COVID-19 pandemic on informal workers, such as taxi drivers, in the second Mexican entity with the most infections; and indicate the public policies directed to this sector. It is a work with a qualitative approach, which uses the techniques of documentary research, the semi-structured interview and observation in the field. The results show a 50% reduction in income, negative emotional effects, and the absence of policies directed at this sector during this health crisis. The need to redefine the characteristics of so-called informal work is concluded, since not all workers in this sector are completely outside the legal framework.
Keywords: pandemic; COVID-19; social policies; taxi drivers; informal work